FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MENERAPKAN TEKNOLOGI USAHATANI PADI ORGANIK DAN DAMPAKNYA TERHADAP PRODUKTIVITAS DAN PENDAPATAN (Kasus Pada Petani di Kecamatan Cibeber, Kabupaten Cianjur) - Alinda Kamil; Euis Dasipah; Karyana KS; Dety Sukmawati; Agi Dahtiar (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to analyze the factors that influence farmers' decisions on the application of organic rice farming and their impact on productivity and income. The respondent determination technique used is a census obtained with a size of 80 people, each of which is 40 people who apply and 40 people who do not apply organic rice farming. The analysis technique used is multiple logistic regression. The results of the study obtained that the performance of organic rice farming was characterized by a land area of 0.44 ha, organic rice farming activities started from the use of superior and certified seeds; land management; Basic and secondary fertilization; use of organic materials; planting seeds; weeding; irrigation; pest and disease control; harvest and post-harvest, all of which are done conventionally. Marketing of the produce is done at the farmer's place with a selling price of Rp. 5,000/kg. Farmers' motivation factors, ease of obtaining organic materials, farming experience, land area, grain selling price, availability of farmer's capital simultaneously significantly influence the decision to implement organic rice farming. Meanwhile, partially, the significant ones with the largest order are: the selling price of grain; farmer motivation; ease of obtaining organic materials; and land area. The application of organic rice farming has no significant effect on productivity gains. For farm land. organic rice yielded 6,977 kg/ha productivity. While the non-organic 6,937 kg/ha. The application of organic rice farming has a positive effect on income, namely Rp. 15.162.464 / ha with R/C = 2.25, while the non-organic is Rp. 14.458.496 / ha with R/C = 1.80.